2023
DOI: 10.1002/adom.202301032
|View full text |Cite
|
Sign up to set email alerts
|

Visible White‐Light Emission and Carrier Dynamics Observed in Full‐Series GaSe1‐xSx (0≤x≤1) Multilayers

Abstract: Near‐band‐edge emissions ranging from red (≈630 to 602 nm) to green (≈550 to 534 nm) and blue (≈494 to 480 nm) colors have been detected in full‐series GaSe1‐xSx (0≤x≤1) multilayers using micro‐photoluminescence (µPL) measurements from 4 to 300 K. The multilayered chalcogenides crystallize in a hexagonal structure, with observed mixed stacking phases of ε and β polymorphs through X‐ray diffraction and Raman measurements. The µPL results, along with experimental band‐edge characterization through thermoreflecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…III–VI layered semiconductors have gained significant attention due to their unique electronic and optical properties as well as specific technological applications. , The III and VI monochalcogenides possess a general chemical formula of MX, where M is a group III element (such as Ga or In), and X is a chalcogen atom (such as Te, Se, or S). One of the most exciting properties of III–VI layered semiconductors is their direct band edge constructed in the multilayer form, this can make them an ideal candidate for various optoelectronics applications such as solar cells, photodetectors, and light-emitting diodes. Indium is easily oxidized and exhibits intriguing characteristics within the group III elements, especially as it forms many compounds by synthesis with group VI elements, such as In–O, , In–S, In–Se, and In–Te. , The formation of In–Se bonding is important in III–VI compounds, and it has been extensively studied and investigated for its derivatives in various applications. ,, The investigation of In–Se-based materials is driven by their potential utilization in various applications, including solar cells, , Li-ion batteries, and ionizing radiation detectors, due to their noteworthy physical features, such as optical and electrical properties . The materials of the In–Se system have also attracted considerable interest due to its intrinsic structural properties, including phase transition (transformation), multicrystalline zones consisting different phases, and structural imperfections. , Extensive research has been conducted on materials derived from the In–Se system, and numerous works have investigated the phase diagram of the In–Se system with different stoichiometry and different modifications. Previous investigations have reported that the presence of stable phases in this In–Se system includes the stoichiometric compositions of InSe, In 2 Se 3 , In 4 Se 3 ,…”
Section: Introductionmentioning
confidence: 99%
“…III–VI layered semiconductors have gained significant attention due to their unique electronic and optical properties as well as specific technological applications. , The III and VI monochalcogenides possess a general chemical formula of MX, where M is a group III element (such as Ga or In), and X is a chalcogen atom (such as Te, Se, or S). One of the most exciting properties of III–VI layered semiconductors is their direct band edge constructed in the multilayer form, this can make them an ideal candidate for various optoelectronics applications such as solar cells, photodetectors, and light-emitting diodes. Indium is easily oxidized and exhibits intriguing characteristics within the group III elements, especially as it forms many compounds by synthesis with group VI elements, such as In–O, , In–S, In–Se, and In–Te. , The formation of In–Se bonding is important in III–VI compounds, and it has been extensively studied and investigated for its derivatives in various applications. ,, The investigation of In–Se-based materials is driven by their potential utilization in various applications, including solar cells, , Li-ion batteries, and ionizing radiation detectors, due to their noteworthy physical features, such as optical and electrical properties . The materials of the In–Se system have also attracted considerable interest due to its intrinsic structural properties, including phase transition (transformation), multicrystalline zones consisting different phases, and structural imperfections. , Extensive research has been conducted on materials derived from the In–Se system, and numerous works have investigated the phase diagram of the In–Se system with different stoichiometry and different modifications. Previous investigations have reported that the presence of stable phases in this In–Se system includes the stoichiometric compositions of InSe, In 2 Se 3 , In 4 Se 3 ,…”
Section: Introductionmentioning
confidence: 99%